Determinants of food label use among supermarket shoppers : a Singaporean perspective - Lwin, May Oo (2013)
Objective: Examining factors influencing food label use among Singapore's supermarket shoppers using the Theory of Planned Behavior. Design: A point-of-purchase survey among general shoppers in 2 supermarkets. Setting: Singapore, a country whose population is exposed to a wide range of food labeling formats because of the import-dependent nature of the food industry. Participants: A total of 200 shoppers (Chinese [75.5%], Malays [8.5%], and Indians [7.0%]) participated in the survey. Main Outcome Measures: Independent variables composed of attitudes and subjective norms (both 5-point Likert); perceived behavioral control and diet-health concern (both 5-point semantic differential); and knowledge (18-item index). Dependent variables were intention to use food labels (5-point differential scale) and actual use of food labels (19-item index). Analysis: Data were analyzed using descriptive statistics, mean analysis, and multivariate linear regression. Results: Low levels of knowledge and health literacy were found. Attitudes, subjective norms, and behavioral control differed significantly by age and ethnicity. Subjective norms and diet-health concern were significant predictors of intention to use food labels. Conclusions and Implications: Lack of knowledge but positive attitudes toward food labels make Singapore's consumers vulnerable to misusing or being misled by food label information. Demographic differences demonstrate the need to develop targeted educational interventions and enhance awareness of and ability to use food labels.